ENGLISH EDUCATION STUDENTS’ USE OF INDONESIAN-ENGLISH CODE SWITCHING ON INSTAGRAM - Lingga Suganda; Ismail Petrus; Anita Aprilianti (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Code switching often occurs in daily conversation of multilingual society, including on their use of social media. This study aims to describe the types, functions, and reasons of code switching made by university students of English Education Department in their Instagram accounts. The data in this study are in the form of caption and comments on the Instagram accounts and the responses from the interview and questionnaire with 61 participants. This study used three instruments, namely documentation, questionnaires, and interviews. The findings indicated that tag switching was the dominantly used type of code switching with directive, poetic, and expressive functions. While, to attract attention, to show habitual expression, to address different audience, and to show mood of the speaker were the functions and reasons of their code switching. Code switching with regards to the certain types, functions, and reasons is used naturally within informal context communication among the youth who know and learn English as a foreign language (EFL) formally.